Periodical Studies Today Multidisciplinary Analyses - Ernst, Jutta; Scheiding, Oliver; von Hoff, Dagmar (Brill, 2022)
Combining theoretical and empirical approaches, this volume offers a wide-ranging survey of periodical research today. It illustrates the shift from content-related investigations and archival recovery to multidisciplinary analyses which consider, for instance, how magazines, newspapers, and other serial print products shape our opinions and help us to form like-minded communities. International specialists explore periodicals as relational artefacts, highlighting editorial constellations, material conditions, translation, design, marketing, and the consumption of newspapers and magazines from the late seventeenth to the twenty-first century. A must-read for academic and interested readers who wish to explore new and relevant ways to analyze periodicals.